(untitled) (Orinoquia, 2022)
Dear Editor, upon carefully reading an interesting article from the Orinoquia magazine, entitled “Productive parameters and digestibility of chickens, using cayenne (Hibiscus rosa-sinensis) and probiotic (Lactobacilius acidophilus) plus pectin” (Mariño and Roa, 2021), I would like to point out a few comments myself. Anders Celsius (Uppsala, Sweden, 1701- Uppsala, 1744) in 1742, just two years prior to his death, designed a scale for temperature where the boiling point would be 0 degrees and the freezing point 100 degrees (reverse to what currently used). This scale was called “degrees centigrade”, “centi” because it had one hundred (100) divisions between both points and “degree” because it is a gradient (CIPM, 2006; Henson, 2015; RAE, 2021). In 1744, after Celsius’ death, his contemporary, Carl von Linné, better known as Carlos Linnaeus (Råshult, Sweden, 05/23/1707- Hammarby, Sweden, 01/10/1778) and who is famous mainly for inventing the binomial nomenclature (genus and species) and by pointing out for the first time the symbols of male () and female (), Linnaeus, saw Celsius scale as impractical. He proposed inverting it, where water would boil at 100 and its boiling point freezing would be 0, maintaining the 100 divisions between both places described, which was quickly accepted by the scientists of the time (CIPM, 2006; Henson, 2015; RAE, 2021). The name of this scale was accepted for 204 years until, in 1948, the Consultative Committee on Thermometry of the General Conference on Weights and Measures (CGPM) replaced “degrees centigrade” with “degrees Celsius” due to the confusion that occurred between the unit of magnitude of temperature and the unit used in the magnitude of the geometric angle, also called “degree centigrade” (angular measure equal to 1/100 of a right angle) since the same name should not be given to two different magnitudes (CIPM, 2006; Henson, 2015). To be more precise, the term “degree Celsius” was adopted in 1948 by the Procès-Verbaux of the International Committee for Weights and Measures, and the 9th Conférence Générale des Poids et Mesures (General Conference on Weights and Measures) in the Comptes Rendus [CIPM, 1948 (PV, 21, 88) and 9th CGPM, 1948 (CR, 64)] (CIPM, 2006; Henson, 2015). In these meetings, the «degree Celsius» (°C) was chosen among the three terms proposed (degree centigrade, degree centesimal and degree Celsius) to designate the temperature. In such a way that it is already 74 years since the adoption of this measure by the 53 Member States and the 41 associated States, including Colombia. Second, in Latin America, the comma “,” must be used instead of the point “.” to separate integers from fractions, since, although both the Royal Spanish Academy of Language and the International Office of Weights and Measures decided to admit both signs to separate integers from decimals (unification). There are other regulations that refer to the comma (,) as the only separating sign for decimals and integers in all languages (CIPM, 2006; Henson, 2015; RAE, 2021). In England and its former colonies such as the United States, Australia and India, they use the point as a decimal separator, while the use of the comma is used in the rest of the countries (the majority), which can be seen in the computer of each user, where according to the regional configuration, the calculator will use the comma or the point as a decimal separator, according to the selected country (CIPM, 2006; Henson, 2015; RAE, 2021).